Tomsk Polytechnic University is the basis of the Central Asia Centre for Engineering Education - Pokholkov Y. P. Yuri Petrovich (2001, 2001)
The Central Asia Centre for Engineering Education (CACEE) has been founded at the Tomsk Polytechnic University (TPU), Tomsk, Russia as a satellite centre of the UNESCO International Centre for Engineering Education (UICEE), which is based at Monash University, Melbourne, Australia. This has been accomplished within the framework of the Memorandum of Understanding between the TPU and the UICEE, which became effective since January 1, 2001. The paper discusses the history and present-day of the TPU as well as the aims and major fields of activities of the CACEE